THE RELATIONSHIP BETWEEN ADIPOSE TISSUE FACTORS AND OBESITY UNDERLYING THE OCCURRENCE OF METABOLIC SYNDROME - R Kusuma; Surjadi Rimbun (Cattleya Darmaya Fortuna, 2025)
The growing prevalence of sedentary lifestyles, particularly in urban populations, combined with the widespread consumption of unhealthy foods, has contributed to increasing rates of overweight and obesity (adiposity). These conditions induce pathophysiological disturbances in adipose tissue, which functions as an endocrine organ, thereby leading to metabolic syndrome. Atherogenic dyslipidemia plays a significant role in the progression of atherosclerosis, ultimately increasing the risk of cardiovascular diseases. Furthermore, inflammatory mediators released by dysfunctional adipocytes are associated with the development of certain types of cancer. This review highlights the role of obesity and adipose tissue as fundamental components in the emergence of metabolic syndrome, aiming to strengthen scientific understanding and encourage further research to develop effective strategies for the prevention and management of complex metabolic disorders